2016
DOI: 10.1080/17425247.2016.1201059
|View full text |Cite
|
Sign up to set email alerts
|

Application of lipid nanoparticles to ocular drug delivery

Abstract: Although eye drops are widely used as drug delivery systems for the anterior segment of the eye, they are also associated with poor drug bioavailability due to transient contact time and rapid washout by tearing. Moreover, effective drug delivery to the posterior segment of the eye is challenging, and alternative routes of administration (periocular and intravitreal) are generally needed, the blood-retinal barrier being the major obstacle to systemic drug delivery. Areas covered: Nanotechnology, and especially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(64 citation statements)
references
References 111 publications
0
63
0
1
Order By: Relevance
“…As controlled release systems, they can reduce the need for frequent intravitreal injections while their small size (<500 nm) may enhance penetration across any rate‐limiting barriers thus providing the potential to deliver therapeutic concentrations to the retinal tissues . Additionally, nanocarriers can remain in the eye for several months after administration maintaining therapeutic concentrations at the target site over longer periods . In this review, we discuss the effectiveness of different nanocarriers reported to date, including polymeric nanosphere, nanocapsules, liposomes, nanomicelles, nanocrystals, and dendrimers, in delivering therapeutic agents to the retinal tissues in a safe and effective manner with reference to recent preclinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…As controlled release systems, they can reduce the need for frequent intravitreal injections while their small size (<500 nm) may enhance penetration across any rate‐limiting barriers thus providing the potential to deliver therapeutic concentrations to the retinal tissues . Additionally, nanocarriers can remain in the eye for several months after administration maintaining therapeutic concentrations at the target site over longer periods . In this review, we discuss the effectiveness of different nanocarriers reported to date, including polymeric nanosphere, nanocapsules, liposomes, nanomicelles, nanocrystals, and dendrimers, in delivering therapeutic agents to the retinal tissues in a safe and effective manner with reference to recent preclinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…9, 10 Lipids, Hyaluronic acid, PEG, PLGA and chitosan are commonly used polymers as topical drug delivery carriers and have been fabricated into particles and hydrogels. 1119 In particular, particle-based colloidal drug delivery systems help overcome the cornea barrier and realize prolonged drug release. 2022 In addition, they do not cause blurriness.…”
Section: Introductionmentioning
confidence: 99%
“…7 Effective topical drug delivery poses a major challenge due to the presence of various elimination mechanisms and physiological barriers that result in low ocular bioavailability. [8][9][10] Increasing the retention time in the precorneal area and improving the permeability across ocular tissues of drugs are two major key aspects to enhance ocular bioavailability. 1 Ban et al developed positively charged chitosan (CTS)-coated solid lipid nanoparticles with high ocular bioavailability, which was ascribed to the electrostatic interaction between the positively charged nanoparticles and the negatively charged ocular surface.…”
Section: Introductionmentioning
confidence: 99%